The Weighted Morrey Boundedness of Multilinear Singular Integral Operators on RD-Spaces (Analysis in Theory and Applications, 2022)
An RD-space $\mathcal{X}$ is a space of homogeneous type in the sense of Coifman and Weiss, which is equipped with a measure satisfying an additional reverse doubling property. In this paper we study the boundedness of multilinear singular integral operators in weighted Morrey spaces within the framework of RD-spaces.